Blame, Damnation, and Evolved Dispositions: A Dilemma. (16th February 2021) - Pedersen, Daniel J.
Abstract: Natural scientists have offered reasons to think that some vile human acts have evolutionary explanations. Christians would describe some of these acts as sins, and indeed as sins potentially worthy of damnation. However, I argue that, on the supposition that such sins have evolutionary causes, the agents who commit these sins are not justly damnable for the acts in question. This is because the justice of damnation minimally depends on two criteria: 1) that sinful acts are properly voluntary; and 2) that asymmetrical fault between sinners and God holds for said acts. Because, on the assumption that dispositions to sin have evolved, one or both of these criteria cannot be sustained, theologians face a choice. They must either affirm the evolutionary origins of some sinful acts and deny damnation in the relevant cases, or, if they wish to affirm damnation in all relevant cases, they must deny that there are evolved dispositions to sin. Whichever way it is resolved, the dilemma is serious and concrete. Because it is serious, it requires careful attention from all theologians, not only theology‐and‐science specialists. Because it is concrete, it cannot be dissolved with methodological strategies alone.